Testing the 'brain gain' hypothesis: Micro evidence from Cape Verde - BATISTA, CATIA; VICENTE, PEDRO (Elsevier, 2011)
Does emigration really drain human capital accumulation in origin countries? This paper explores a unique household survey purposely designed and conducted to answer this research question. We analyze the case of Cape Verde, a country with allegedly the highest `brain drain? in Africa, despite a marked record of income and human capital growth in recent decades. Our micro data enables us to propose the first explicit test of `brain gain? arguments, according to which the prospects of own future migration can positively impact educational attainment. Our most conservative estimates using individual specific variation in economic conditions at the destination indicate that a 10 pp increase in the probability of own future migration improves the probability of completing intermediate secondary schooling by nearly 4 pp for individuals who do not migrate before age 16. These findings are robust to the choice of instruments and econometric specification. Counterfactual simulations point to significant human capital gains from lowering migration barriers.
PUBLISHED
Keywords: Economics; International migration